IMPROVING THE EFFECTIVENESS OF TREATMENT IN ACUTE SENSORINEURAL HEARING LOSS (Multidisciplinary Journal of Science and Technology, 2025)
Acute sensorineural hearing loss (ASNHL) remains one of the pressing issues in otorhinolaryngology due to its sudden onset and high risk of persistent hearing0020impairment. This article examines modern and innovative approaches to the treatment of ASNHL, including the combined use of glucocorticoids, vascular agents, and neuroprotective drugs. An analysis of clinical data and literature review allows for the identification of the most effective treatment regimens aimed at improving auditory function and reducing the risk of long-term disability in patients.